2018
DOI: 10.1111/jcpe.12995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bifidobacterium probiotic on the treatment of chronic periodontitis: A randomized clinical trial

Abstract: AimThis randomized placebo‐controlled clinical trial evaluated the effect of Bifidobacterium animalis subsp. lactis (B. lactis) HN019‐containing probiotic lozenges as adjuvant to scaling and root planing (SRP) in patients with generalized chronic periodontitis.Materials and MethodsForty‐one chronic periodontitis patients were recruited and monitored clinically, immunologically, and microbiologically at baseline (before SRP) and 30 and 90 days after SRP. All patients were randomly assigned to a Test (SRP + Prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
231
2
28

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(272 citation statements)
references
References 47 publications
(75 reference statements)
11
231
2
28
Order By: Relevance
“…Mixed outcomes were also observed with the use of adjunctive probiotics in the treatment of periodontal diseases, although most studies did show positive clinical results. For chronic periodontitis patients, most studies found significant clinical improvements in periodontal pocket depth, especially in the deeper periodontal pocket depth, clinical attachment level, bleeding on probing, sulcus bleeding index, gingival and plaque indices, and/or percentage of sites with plaque following the adjunctive use of probiotics . As a result of these improved clinical parameters, some studies found a decreased need for periodontal surgery .…”
Section: Probiotics As Adjunctive Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed outcomes were also observed with the use of adjunctive probiotics in the treatment of periodontal diseases, although most studies did show positive clinical results. For chronic periodontitis patients, most studies found significant clinical improvements in periodontal pocket depth, especially in the deeper periodontal pocket depth, clinical attachment level, bleeding on probing, sulcus bleeding index, gingival and plaque indices, and/or percentage of sites with plaque following the adjunctive use of probiotics . As a result of these improved clinical parameters, some studies found a decreased need for periodontal surgery .…”
Section: Probiotics As Adjunctive Treatmentmentioning
confidence: 99%
“…Several studies also found that adjunctive probiotics in the treatment of chronic periodontitis improved host response parameters. Specifically, probiotics improved or lowered the levels of matrix metalloproteinase‐8, tissue inhibitor of metalloproteinase‐1, and pro‐inflammatory cytokines, including tumor necrosis factor‐alpha, interleukin‐1beta, and interleukin‐17 …”
Section: Probiotics As Adjunctive Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics thus have an immunomodulatory effect on the host immune system (Dar, Shukla, et al., ). First clinical evidence supports the concept that probiotic‐induced immunomodulation can prevent alveolar bone loss (Ikram, Hassan, Raffat, Mirza, & Akram, ; Invernici et al., ). For example, B. lactis decreased probing pocket depth, periodontal pathogens, pro‐inflammatory cytokines and increased clinical attachment gain (Invernici et al., ).…”
Section: Preamblementioning
confidence: 79%
“…First clinical evidence supports the concept that probiotic‐induced immunomodulation can prevent alveolar bone loss (Ikram, Hassan, Raffat, Mirza, & Akram, ; Invernici et al., ). For example, B. lactis decreased probing pocket depth, periodontal pathogens, pro‐inflammatory cytokines and increased clinical attachment gain (Invernici et al., ). Thus, the microbiome can set the threshold of inflammation including the T cells thereby becoming a candidate for therapeutic intervention and diagnosis.…”
Section: Preamblementioning
confidence: 79%